Progress in the Study of Colorectal Cancer Caused by Altered Gut Microbiota After Cholecystectomy - Ma, Yanpeng; Qu, Ruize; Zhang, Yi; Jiang, Changtao; Zhang, Zhipeng; Fu, Wei (Frontiers in Endocrinology, 2022)
Epidemiological studies have found an increased incidence of colorectal cancer (CRC) in people who undergo cholecystectomy compared to healthy individuals. After cholecystectomy, bile enters the duodenum directly, unregulated by the timing of meals. Disruption of the balance of bile acid metabolism and increased production of primary bile acids, which in turn affects the composition and abundance of intestinal microorganisms. The link among cholecystectomy, the gut microbiota, and the occurrence and development of CRC is becoming clearer. However, due to the complexity of the microbial community, the mechanistic connections are less well understood. In this review, we summarize the changes of gut microbiota after cholecystectomy and illuminate the potential mechanisms on CRC, such as inflammation and immune regulation, production of genotoxins, metabolism of dietary ingredients, activation of signaling pathways, and so on. By reviewing these, we aimed to unravel the interactions between the gut microbiota and its host and be better positioned to develop treatments for CRC after cholecystectomy.